GREEN VILLAGE DAN CIRCULAR ECONOMY : OPTIMALISASI EKONOMI LOKAL MELALUI EDUWISATA DAN INOVASI KEWIRAUSAHAAN HIJAU DI DESA SIMPANG, KABUPATEN TASIKMALAYA - Alfin Nur Arifah; Rizky Ridwan; Aditia Abdurachman; Dheri Febiyani Lestari; Nurherawati (Jurnal Abdi Masyarakat, 2025)
This community engagement program aimed to develop sustainable tourism in Simpang Village, Bantar Kalong District, Tasikmalaya Regency, by enhancing human resource capacity through the establishment of a Tourism Awareness Group (Pokdarwis). Based on field observations, Cibeureum Dam was identified as a potential tourist destination that had not been optimally utilized due to legal disputes and lack of structured management. The program included activities such as stakeholder meetings, environmental clean-up, Pokdarwis formation, tourism training, digital promotional content creation, and the launching of a camping ground tourism concept. These initiatives encouraged local participation and built community awareness on managing tourism sustainably. Despite challenges such as limited public enthusiasm and unresolved land ownership, the program successfully laid the foundation for inclusive, environmentally conscious tourism development rooted in local potential